The importance of production and tendency on halal products and services in Malaysia and global market / Omar Adli Mohd Azmi and Shafika Mihat - Mohd Azmi, Omar Adli; Mihat, Shafika (2013)
This is a study about the importance and tendency on Halal products and services in Malaysia and Global Market. In global market, consumer base for Halal products is around 1.7 billion people worth more than 2.3 trillion dollar. It makes the Halal market vitally important emerging sector that should not be overlooked. From the market perspective, traditional target market remains in Asia and Middle East, however due to the effect of globalization there are significant development of market size for Halal market in Europe and USA. Besides that in Western country, most Halal product is still not readily available for UK market. We see this phenomena applying not only on food items. Personal hygiene and healthcare products, toiletries and cosmetics are all appearing as Halal options. Once Halal is understood as a lifestyle choice, the range of option for Halal product will increase exponentially. In Malaysia, Halal products is not a big issue as we can find Halal food everywhere from the street market up to the high end chain. The competition can be considered intense in the market.